The Impact of COVID-19 on Domestic Tourism by Older People in Taiwan - Chan, Ching-Tang (Frontiers in Public Health, 2022)
Taiwan's older population (those over the age of 65) reached 3.95 million at the end of January 2022, accounting for around 16.9% of the country's total population. It is already an “aged society.” With the gradual increase in the older population, the older people tourism market is also getting more and more attention. This article explores how older people tourism was affected by the COVID-19 pandemic (present in Tawian from early 2020), which was a major international public health event. This study adopts quantitative and PCA methods to statistically analyze the changes before and after the pandemic. The study results found that the frequency of tourism decreased after the pandemic: the number was 5.32, a decrease of 0.77, and instances of at least 1 tourist trip decreased by 3.87% after the pandemic. Regarding the reasons for not participating in tourism, during the COVID-19 pandemic, the COVID-19 accounted for a factor of 19.9%. Total travel expenses were NT2,590, an increase of NT229.67, and were not affected by the pandemic. We carried out a PCA analysis on tourism spending. The first component was food, accommodation, shopping, and other expenses. The factor loadings were 0.989, 0.931, 0.641 and −0.948, respectively. The second component was entertainment and transportation expenses. The factor loadings were 0.997 and 0.902, respectively. In conclusion, we put forward relevant discussions and suggestions to make tourism for older people healthier and more sustainable.